Malicious Cyber Attacks - Iamandi , Luca; Virgolici , Ionel Vladimir; Ionita, Alina Melania; Draganescu , Alexandru (Journal of Danubian Studies and Research, 2022)
Information plays a vital role in the development of human society, an element that cannot be neglected in interpersonal relationships. The use of information technologies in all fields has proven its effectiveness through the speed and efficiency with which activities are carried out. This makes cybercrime play an increasingly important role in organized crime. To counter this phenomenon, states must improve their IT systems and technologies, while at the same time creating a legal framework that criminalizes all antisocial acts generated through information technologies. Also, more attention should be paid to the training of those who are involved in combating this phenomenon and the appropriate information of the people who use the computer systems, thus creating a stronger security barrier against this type of crime.